Sustainable Garden: Strategic teaching project as proposed in Environmental Education (Research, Society and Development, 2022)
The present work aimed to report the processes and results of a sustainable garden project developed in a sustainable educational space applied with teaching practices in a way that allowed the use of different approaches that favored the construction of theoretical and practical knowledge related to sustainability issues, environment and healthy eating as a strategy in environmental education, encouraging mobilization towards the dissemination and multiplication of information in our society, which is one of the first steps towards building an educational process. And through that, it was possible to obtain results through observations and interventions of actions that contributed to the teaching of Science, which made it possible for students to know and understand the reality in which they are inserted. The project had direct participation of the students where they were responsible for the satisfactory result for presenting improvement in the teaching and learning process by means of provided knowledge, changes in habits throughout this project, such as the awareness of the importance of reuse, recycling and the reduction of materials recyclables used, as well as the search for quality of life, well-being and preservation of the environment. In this context, it is important to emphasize that with the execution of the project it was possible to build a closer relationship between the theoretical and practical classes used in the face of the acquired skills, knowledge about the importance of obtaining a management technique for a healthy diet and free from the use of pesticides. , focusing on the development among the disciplines, reaching to collaborate an interdisciplinary transformation and social inclusion.